Akibat Hukum Pelaku Usaha Terhadap Produk Pangan Yang Tidak Bersertifikasi Halal - Citra, Andita Nara; Widyanti, Ikarini Dani (Pusat Kajian Hukum Perbankan Fakultas Hukum Universitas Jember, 2023)
Abstract : Every pangan product made in Indonesia must have a halal certification before being sold to the general public. Halal certification is accomplished by applying a halal label to products that are produced and by including a halal declaration in the packaging. This action is intended to encourage the general population who do not consume unhealthy food to do so (haram). It is stated in Pasal 4 Undang-Undang No. 33 Tahun 2014 about Jaminan Produk Halal that products that are imported into, are manufactured in, and are distributed in Indonesia must be certified as halal. On the other hand, there are a lot of foods that are sold in stores that lack halal certification. The purpose of this study is to understand how the hukum that was expressed by the owner of a business selling pangan without a certification that it was permissible under Islamic and positive law. Keywords : owner of a business; food product; certified halal.